Fitness cost and competitive disadvantages of a G143A mutant Alternaria alternata on tangerine resistant to QoI fungicides - Dorigan, Adriano Francis; Moreira, Silvino Intra; Condé, Thiago Oliveira; da Silveira, Patricia Ricardino; Pinheiro, Indiara Carol Lopes; Ceresini, Paulo Cezar [UNESP]; Alves, Eduardo (Springer Nature, 2025)
Quinone outside inhibitor (QoI) fungicides have been used intensively in the management of Alternaria brown spot (ABS) disease caused by Alternaria alternata on tangerine. The aim of this study was to investigate fitness variables and competitive abilities of mixtures of resistant (QoI-R) and sensitive (QoI-S) A. alternata isolates. Fitness variables including oxidative stress in vitro, incubation period, disease severity and conidial production on tangor leaves were not significantly different between the QoI-R and QoI-S isolate groups. The in vitro assays revealed that the QoI-R isolates group had higher EC50 for azoxystrobin and pyraclostrobin, higher conidial germination, higher mycelial growth in PDA and higher conidial production. However, the QoI-R isolates group was also highly sensitive to osmotic stress. The in vivo competition test indicated a competitive disadvantage of the QoI-R isolate in comparison with the QoI-S isolate as a lower number of resistant conidia were harvested from ABS lesions even on leaves inoculated with mixtures containing higher proportions of QoI-R conidia. These results provide evidence of fitness costs and competitive disadvantages of the A. alternata mutant cytb-G143A.
Keywords: Alternaria brown spot; Azoxystrobin; Citrus reticulata Blanco; Pyraclostrobin; Quinone outside inhibitors